A new mtDNA mutation associated with Leber hereditary optic neuroretinopathy. - Huoponen, K (1991)
A single base mutation at nucleotide position 3460 (nt 3460) in the ND1 gene in human mtDNA was found to be associated with Leber hereditary optic neuroretinopathy (LHON). The G-to-A mutation converts an alanine to a threonine at the 52d codon of the gene. The mutation also abolishes an AhaII restriction site and thus can be detected easily by RFLP analysis. The mutation was found in three independent Finnish LHON families but in none of the 60 controls. None of the families with the nt 3460 mutation in ND1 had the previously reported nt 11778 mutation in the ND4 gene. The G-to-A change at nt 3460 is the second mutation so far detected in LHON.